A thermal management of Darcy-Forchheimer SWCNT-MWCNT Cross hybrid nanofluid flow due to vertical stretched cylinder with and without inertia effects - Sahu, S. K.; Shaw, S.; Thatoi, D. N.; Nayak, M. K. (Waves in random and complex media, 2025)
Heat transfer from a surface enshrouded in a porous medium through which non-Newtonian hybrid nanofluid is flowing is of great practical importance in several fields of engineering. Cross fluid model is implemented due to its significant properties like yield stress features, flow in regions of both low and high shear rates, finite viscosity and time constant. Especially, convective flows in a porous medium are of considerable interest in view of the present and potential utilization of geothermal energy, solar energy, etc. for power production. The purpose of this paper is to present the numerical solutions of boundary-layer equations describing the steady free convection flow of non-Newtonian hybrid nanofluid in a saturated porous medium described by Forchheimer extended Darcy's law. Flow and heat transfer characteristics with and without inertia effects are explored. Percentage of heat transfer rate (HTR) enhancement is obtained. The major outcomes of the study are that velocity of Cross hybrid nanofluid exhibits opposite effects in response to amplification of Weissenberg number and porosity parameter in both presence and absence of inertia. The heat transfer rate for quadratic radiation contributes to moderate response. Further, percentage enhancement of heat transfer rate is greater subject to disparate Weissenberg number compared to that of Brinkman number.